Judicial and legal policy of Ekaterina Ii in the Western Kazakhstan: purposes, contents, results (Journal of actual problems of jurisprudence, 2019)
The judicial law policy of the Russian Empire in the territory of the Western Kazakhstan at the end of the XVIII centurywas directed on legal submission of the steppe population, systematic settling border conflicts and establishment oflegal communications between the Kazakh and Russian population. In this article are investigated purposes, principles,ways and results of realization of judicial law policy of Ekaterina II. The work is performed on the basis of the complexanalysis of sources.Key words: court history, the Russian empire, Junior Kazakh juz.